S100 and CD34 positive spindle cell tumors of the uterine cervix with EGFR mutation: a hitherto unrecognized neoplasm phenotypically and epigenetically overlapping with "NTRK-rearranged spindle cell neoplasms" of the uterus - Michal, Michael; Kuruc, Josef; Hájková, Veronika; Michalová, Květoslava; Klubíčková, Natálie (Virchows Archiv, 2025)
NTRK-rearranged spindle cell neoplasm represents an emerging entity included in the latest 5th edition of WHO classification of both soft tissue and female genital tumors. By immunohistochemistry, they are commonly positive for CD34, S100 protein, and CD30 and typically harbor fusions of kinase genes such as NTRK1/2/3, RET, and BRAF. In the gynecological tract, they typically affect the uterine cervix or uterine body. Most of the reported cases had fibrosarcoma-like morphology, occasionally showing perivascular and stromal hyalinization with only a few cases showing a less cellular spindle cell proliferation. Except for one case with RET fusion, all other gynecological cases harbored exclusively NTRK1/2/3 fusions. Besides kinase gene fusions, the analogous tumors in soft tissues may also harbor activating EGFR or BRAF point mutations, but no such case has been described in the uterus. Herein we are reporting two cases from the uterine cervix showing morphology and molecular features previously unreported at this anatomic site. The patients were 46 and 34 years old and clinically presented with unremarkable cervical polyps each measuring 8 mm in diameter. Histologically, both cases had a rounded polypoid outline and were composed of hypocellular proliferation of bland spindle cells lacking mitotic activity and growing in a fibrotic stroma which was punctuated by prominent small vessels with thick hyalinized walls. Immunohistochemically, both showed a diffuse expression of CD34, CD30, and S100 protein, whereas SOX10 was negative. Both cases harbored exon 20 EGFR mutation and did not reveal any fusions or significant copy number changes. The patient in case 1 was treated by hysterectomy with salpingectomy with no other residual tumor detected, and she was alive and well 27 months after the diagnosis. The patient in case 2 had no other known tumors at the time of diagnosis, but no follow-up is available. We believe the reported cases represent a hitherto unrecognized variant of "NTRK-rearranged spindle cell neoplasms" of the uterine cervix with novel EGFR mutations.
Keywords: receptor trkA; genová přestavba; S100 and CD34 co-expression; Uterine Neoplasms; lidé; imunohistochemie; EGFR mutation; NTRK-rearranged spindle cell neoplasms; Middle Aged; ErbB Receptors; mutace; Soft tissues; Antigens, CD34; Adult; nádory děložního čípku; fenotyp; Gene Rearrangement; Biomarkers, Tumor; proteiny S100; Uterine cervix; Immunohistochemistry; Phenotype; ženské pohlaví; nádorové biomarkery; nádory dělohy; Mutation; Humans; S100 Proteins; lidé středního věku; Uterine Cervical Neoplasms; Perivascular and stromal hyalinization; dospělí; antigeny CD34; Female; erbB receptory; Receptor, trkA